ISOLASI BAKTERI ASAM LAKTAT ASAL JUS NANAS SEBAGAI KANDIDAT PROBIOTIK - Cynthia Rizka Riani; Lilis Nuraida; Anja Meryandini (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2020)
Lactic acid bacteria (LAB) are the main group of probiotic bacteria that widely used in fruit juice fermentation products. Fruit juice contains antioxidants that can prevent free radicals. The objective of this study was to identify LAB isolated from pineapple juice that possess probiotic properties and to analyze the antioxidant activity of pineapple juice after being fermented with the LAB. LAB isolates from pineapple juice were evaluated for their probiotic properties (tolerance to acidic conditions and bile salts, antimicrobial activity against pathogenic bacteria, and sensitivity to antibiotics) and their adherence properties (autoaggregation, coaggregation, and hydrophobicity). The best isolates obtained are then inoculated into pineapple juice. From 5 types of pineapple juice, 5 isolates with LAB characteristics were obtained, i.e NHC6, NHC7, NHC8, NHC9, and NPC1. Isolate NHC6 had a good tolerance to acidic conditions (pH 2) and 0,5% bile salt, had antimicrobial activity, was sensitive to ampicillin, showed the best adherance properties and was identified as Lactobacillus plantarum. L. plantarum NHC6 was then added to pineapple juice. Addition of L. plantarum NHC6 to pineapple juice reduced the ᵒBrix and pH values during incubation. After 24 hours of incubation, the antioxidant activity was 89,05%, with LAB growth of 8,33 log CFU/mL, thus 24 hours incubation was considered the best fermentation time for pineapple juice.